System requirement specifications for a semantic knowledge management system for collaborative learning environment - Che Cob, Zaihisma; Abdullah, Rusli; Mohd Drus, Sulfeeza; Ali, Nor'ashikin (2016)
In this study, a Semantic KMS Model is formulated to support collaborative learning environment based on ontology.A comprehensive review was conducted to identify the important components of existing models in Knowledge Management (KM), KMS and semantic areas, and a survey was conducted to finalize the important components of the proposed model.As a result, the proposed semantic KMS model consisted of six important components to support collaborative works; KM Processes, Ontology-based Knowledge Model, Semantic KM Features, Knowledge Quality, System Quality and KM Goals.A prototype, called Semantic KMS for Collaborative Learning was developed to illustrate how the model components are supporting KM processes in collaborative works based on the system requirement specifications described in this paper.The required modules of the semantic KMS are described in details and the ontology-based knowledge models are also presented.